Genetic relationship of tropical region‐bred temperate japonica rice (Oryza sativa) plants and their grain yield variations in three different tropical environments - Lee, Jeom‐Sig; Torollo, Gideon; Ndayiragije, Alexis; Berchmans Bizimana, Jean; Choi, Il‐Ryong; Gulles, Alaine; Yeo, Un‐Sang; Jeong, O‐Young; Venkatanagappa, Shoba; Kim, Bo‐Kyeong; Ahn, Sang Nag (Plant breeding, 2018)
Temperate japonica rice (Oryza sativa) is usually grown in temperate regions. When grown in tropical areas, most temperate japonica rice plants flower prematurely and do not show sufficient vegetative growth. Fourteen japonica rice varieties and lines adapting to tropical environments were developed in the Philippines (tropical Asia) between 2008 and 2014. Their genomes were characterized by genomewide single nucleotide polymorphism genotyping, and their grain yields were examined in the Philippines during the wet and dry seasons and in a high‐altitude area of Burundi (tropical Africa). Based on the genotyping, all 14 materials were found to belong to the temperate japonica rice group. Grain yields were more affected by the environment than by the genotypes. Two of the fourteen rice materials showed more stable and higher yields than the check varieties across the three environments, and one of the two has been released as a commercial variety in the Philippines. Together, these results demonstrate that rice plants genetically belonging to the temperate japonica group can be bred to adapt to tropical areas.